HLA associations in South Asian multiple sclerosis. (January 2016) - Pandit, Lekha; Malli, Chaithra; Singhal, Bhim; Wason, James; Malik, Omar; Sawcer, Stephen; Ban, Maria; D'Cunha, Anitha; Mustafa, Sharik
Background: Previous efforts to identify Human Leukocyte Antigen (HLA) gene associations with multiple sclerosis (MS) in the South Asian population have been underpowered. Aim: To identify the primary HLA class II alleles associated with MS in Indians. Methods: We typed HLA-DRB1, -DQA1 and -DQB1 in 419 patients and 451 unrelated controls by polymerase chain reaction using sequence specific oligonucleotide probes (PCR-SSOP). Results: At the gene level DRB1 showed significant evidence of association ( p =0.0000012), DQA1 showed only marginal evidence of association ( p =0.04) and there was no evidence for association at DQB1 ( p =0.26). At the DRB1 locus association is confirmed with the *15:01 ( p =0.00002) and the *03 ( p =0.00005) alleles. Conclusion: Our study confirms that the risk effects attributable to the HLA- DRB1*15:01and DRB1*03 alleles seen in Europeans are also seen in Indians. The absence of any evidence of association with DQB1 alleles reflects the lower linkage disequilibrium between DQB1 alleles and DRB1 risk alleles present in this population, and illustrates the potential value of fine mapping signals of association in different ethnic groups.